Preliminary report of "Arctic Airborne Measurement Program 2002" (AAMP02) - Yamanouchi, Takashi; Wada, Makoto; Shiobara, Masataka; Morimoto, Shinji; Asuma, Yoshio; Yamagata, Sadamu; Yamazaki, Takashi; Ishidoya, Shigeyuki; Kawahara, Taku; Yabuki, Masanori; Inomata, Yayoi; Herber, Andreas; et al. (National Institute of Polar Research, 2003)
P(論文) The Arctic Airborne Measurement Program 2002(AAMP 02) campaign was carried out in March 2002 as one of the sub programs of the project Variations of atmospheric constituents and their climate impact in the Arctic". The main goal of the project was to investigate the transport, transformation and radiative effect of trace gases and aerosols, and their role in the global climate. An instrumented jet plane, Gulfstream II(G-II), was flown from Nagoya, Japan via Barrow, Alaska to Longyearbyen(78°N , 15°E ), Svalbard, crossing the Arctic Ocean in the lower stratospher. Three local flights were made over the Greenland Sea around Svalbard and two profile flights near Barrow. The plane was equipped with CO_2 and ozone analyzers, gas and aerosol sampling systems, aerosol particle counter, nephelometer, absorption photometer, PMS particle probes, sunphotometer, dew point hygrometer and dropsonde system. During the campaign, intensitive surface operations were also conducted at Ny-Ålesund(79°N , 12°E ), Svalbard. Vertical profiles of several trace gases gave information about transport, a new observation by sunphotometer derived an aerosol optical depth in the stratosphere, and another new observation by dropsonde gave information on the polar vortex. departmental bulletin paper